Virtual Reality Job Interview Training in Adults with Autism Spectrum Disorder - Smith, Matthew J.; Ginger, Emily J.; Wright, Katherine; Wright, Michael A.; Taylor, Julie Lounds; Humm, Laura Boteler; Olsen, Dale E.; Bell, Morris D.; Fleming, Michael F. (Journal of autism and developmental disorders, 2014)
The feasibility and efficacy of virtual reality job interview training (VR-JIT) was assessed in a single-blinded randomized controlled trial. Adults with autism spectrum disorder were randomized to VR-JIT ( n = 16) or treatment-as-usual (TAU) ( n = 10) groups. VR-JIT consisted of simulated job interviews with a virtual character and didactic training. Participants attended 90 % of laboratory-based training sessions, found VR-JIT easy to use and enjoyable, and they felt prepared for future interviews. VR-JIT participants had greater improvement during live standardized job interview role-play performances than TAU participants ( p = 0.046). A similar pattern was observed for self-reported self-confidence at a trend level ( p = 0.060). VR-JIT simulation performance scores increased over time ( R 2 = 0.83). Results indicate preliminary support for the feasibility and efficacy of VR-JIT, which can be administered using computer software or via the internet.